Dynamics of anti-Müllerian hormone during controlled ovarian stimulation. (February 2014) - Böttcher, Bettina; Tsybulyak, Iryna; Grubinger, Thomas; Wildt, Ludwig; Seeber, Beata
Abstract Aim: To evaluate the dynamics of anti-Müllerian hormone (AMH) during controlled ovarian stimulation (COH) and to correlate changes in AMH to age, estradiol (E2) levels, and the presence of polycystic ovary syndrome (PCOS). Methods: Data were retrospectively collected from women presenting for COH in the outpatient clinic of a university hospital between January and July 2011. Concentrations of AMH and E2 during COH with gonadotropins for in vitro fertilization (IVF) (n = 68) and clomiphene or low-dose gonadotropin stimulation cycles (n = 27) for intrauterine insemination were evaluated. Percentage change in AMH and E2 from pre-stimulation values was calculated. Dynamics of hormonal changes were analyzed using non-parametric tests. Correlations between changes in AMH and E2 were analyzed with Spearman correlation. Results: During IVF stimulation, AMH declined steadily from pre-stimulation values. No significant change in AMH dynamics was observed during clomiphene or low-dose stimulation cycles. Percentage decline in AMH during IVF stimulation correlated with rise in E2 at all time points. Conclusions: The observed phenomena contribute to an improved understanding of AMH expression and its role in the follicular development. Our data support the concept that AMH is produced by secondary, preantral and small antral follicles in the early part of stimulation and declines as these follicles are recruited into dominant growing follicles.